ESRA19-0371 What about us? We must be prepared to become a second victim. (30th August 2019) - Lorenzo, YF; de la Quintana, B; Rojas, R; Lombardo, L
Abstract : Background and aims: Adverse events (AEs) are an inherent component of our practice. They cause harm to patients (first victims) and disturbance to the professionals involved in them (second victims). We have developed a safety culture trying to minimize AEs, but many of us are still unprepared for the emotional responses that these events can evoke. Methods: We report a case of a 56-year-old man who developed Streptococcus salivarius meningitis within 16 h after an uncomplicated knee arthroscopy performed during spinal anesthesia. Results: His evolution was very good. After 48 hours of intravenous antibiotic treatment, there were not any symptoms. He left hospital one week later without any kind of sequels. His anesthesiologist, on the other hand, had to confront an internal investigation for weeks finding it tough to come back to the operation room for some days. She described sleeping difficulties, anger, remorse, intrusive memories, anxiety and tachycardia when performing the same technique. The support of her peers was key for her recovery. Conclusions: In Spain, we can extrapolate that 1.5% of the health workers will be involved in one AE per year. Although we do not have enough data, anesthesiologists are possibly at higher risk. 2% of professionals involved in an AE leave the profession. As anesthesiologists, we are prepared to avoid an AE, but few hospitals and even fewer anesthesiology departments have developed organizational support programs for the second victims. We need to design protocols and guidelines for assistance after an AE and to acquire the skills to confront the aftermath.